ANALYSIS OF WATER SALINITY LEVEL OF FREQUENCY MOLTING IN VANNAMEI SHRIMP (LITOPENAEUS VANNAMEI) ABLATED - Salsabiela, Mutiara Salsabiela (Journal of Green Science and Technology, 2020)
Media salinity is a masking factor that plays an important role in controlling the process of shrimp molting and osmoregulation. Both of them are ecophysiological factors for shrimp life, so it is necessary to know the optimum level or range of media salinity for each phase of the molting phase changes in the stage and osmoregulation phase. This study was conducted to examine the molting frequency of adult L. vannamei which was ablated and cultivated at various levels of salinity. This research was carried out for 60 days. This study uses experimental laboratory methods with a systematic randomized design (RAS) with 4 treatments and 3 replications in each treatment. The treatments tested were salinity with S1 treatments (10 ppt, 289.20 mOsm / l postmolt H2O isosmotic), S2 (15 ppt, 432.80 mOsm / l H2O initial intermolt isosmotic), S3 (25 ± 1 ppt, 725, 15 mOsm / l H2O isosmotic final intermolt) and S4 (29 ± 1 ppt, 820.10 mOsm / l H2O isosmotic molt). Data were analyzed with ANOVA. Meanwhile, the difference in effect between treatments was obtained through Duncan's multiple area test. ANOVA results showed that various levels of isoosmotic media salinity at various molting phases had an influence (p <0.05) on molting frequency. The best value of molting frequency was in the S4 treatment (29 ± 1 ppt) (close to isoosmotic molt) 10 times. In the maintenance of L. vannamei which is affixed, it should pay attention to the needs of isoosmotic media, namely media with a salinity of 25 ± 1-29 ± 1 ppt (final intermolt isoosmotic range / premolt to molt). the difference in effect between treatments was obtained through Duncan's multiple region test. ANOVA results showed that various levels of isoosmotic media salinity at various molting phases had an influence (p <0.05) on molting frequency. The best value of molting frequency is in the treatment of S4 (29 ± 1 ppt) (close to isoosmotic molt) 10 times. In the maintenance of L. vannamei which is affixed, it is better to pay attention to the needs of isoosmotic media, ie media with a salinity of 25 ± 1-29 ± 1 ppt (final intermolt isoosmotic range / premolt to molt). the difference in effect between treatments was obtained through Duncan's multiple region test. ANOVA results showed that various levels of isoosmotic media salinity at various molting phases had an influence (p <0.05) on molting frequency. The best value of molting frequency is in the treatment of S4 (29 ± 1 ppt) (close to isoosmotic molt) 10 times. In the maintenance of L. vannamei which is affixed, it is better to pay attention to the needs of isoosmotic media, ie media with a salinity of 25 ± 1-29 ± 1 ppt (final intermolt isoosmotic range / premolt to molt). The best value of molting frequency was in the S4 treatment (29 ± 1 ppt) (close to isoosmotic molt) 10 times. In the maintenance of L. vannamei which is affixed, it is better to pay attention to the needs of isoosmotic media, ie media with a salinity of 25 ± 1-29 ± 1 ppt (final intermolt isoosmotic range / premolt to molt). The best value of molting frequency is in the treatment of S4 (29 ± 1 ppt) (close to isoosmotic molt) 10 times. In the maintenance of L. vannamei which is affixed, it is better to pay attention to the needs of isoosmotic media, ie media with a salinity of 25 ± 1-29 ± 1 ppt (final intermolt isoosmotic range / premolt to molt). Keyword : Salinity, Osmoregulation, Molting, L. vannamei, Ablation.